Formation of Intellectual Abilities in Students on the Basis of a Metacognitive Approach (Eurasian Scientific Herald, 2023)
The place of intellectual abilities in the professional structure, the qualifications of students. The results of intellectual research and the abilities of students and ways of their formation.